Lung imaging during acute chest syndrome in sickle cell disease: computed tomography patterns and diagnostic accuracy of bedside chest radiograph. Issue 2 (7th August 2013) - Mekontso Dessap, Armand; Deux, Jean-François; Habibi, Anoosha; Abidi, Nour; Godeau, Bertrand; Adnot, Serge; Brun-Buisson, Christian; Rahmouni, Alain; Galacteros, Frederic; Maitre, Bernard
Abstract : Introduction: The lung computed tomography (CT) features of acute chest syndrome (ACS) in sickle cell disease patients is not well described, and the diagnostic performance of bedside chest radiograph (CR) has not been tested. Our objectives were to describe CT features of ACS and evaluate the reproducibility and diagnostic performance of bedside CR. Methods: We screened 127 consecutive patients during 166 ACS episodes and 145 CT scans (in 118 consecutive patients) were included in the study. Results: Among the 145 CT scans, 139 (96%) exhibited a new pulmonary opacity and 84 (58%) exhibited at least one complete lung segment consolidation. Consolidations were predominant as compared with ground-glass opacities and atelectasis. Lung parenchyma was increasingly consolidated from apex to base; the right and left inferior lobes were almost always involved in patients with a new complete lung segment consolidation on CT scan (98% and 95% of cases, respectively). Patients with a new complete lung segment consolidation on CT scan had a more severe presentation and course as compared with others. The sensitivity of bedside CR for the diagnosis of ACS using CT as a reference was good (>85%), whereas the specificity was weak (<60%). Conclusions: ACS more frequently presented on CT as a consolidation pattern, predominating in lung bases. The reproducibility and diagnostic capacity of bedside CR were far from perfect. These findings may help improve the bedside imaging diagnosis of ACS.